Factors associated with the lifestyle of state basic education teachers of state during the pandemic - Alexandre dos Reis Vieira; Jorge Luiz Bento de Andrade Junior; Lucas Linhares Costa; Rafaela Borges Teixeira; Vinicius de Paula Arruda Vieira; Tatiana Almeida de Magalhães; Nayra Suze Souza e Silva; Desirée Sant’Ana Haikal; Rosângela Ramos Veloso Silva; Lucinéia de Pinho (Revista Gaúcha de Enfermagem, 2023)
ABSTRACT Objective: To analyze the prevalence and factors associated with the lifestyle profile of public basic education teachers in Minas Gerais during the COVID-19 pandemic. Method: Epidemiological websurvey carried out with public basic education teachers in Minas Gerais. Data collection took place from August to September2020 via digital form. Anthropometric, sociodemographic, work, and lifestyle characteristics were evaluated. Poisson Regression was used. Results: 15,641 teachers participated and 31.1% had inadequate health habits. There was a higher prevalence among men (PR=1.38; 95%CI:1.31;1.45), older age (PR=1.20; 95%CI: 1.07;1.34), greater weekly workload (RP=1.10; 95%CI:1.03;1.17) and those dissatisfied with work (RP=1.21; 95%CI:1.15;1.27). As a protective factor, professors with longer teaching experience (RP=0.92; 95%CI:0.87;0.98) and those hired or appointed (PR=0.89; 95%CI:0.85) ;0.94). Conclusion: Lifestyle inadequacy was found among older male teachers, with longer working hours and job dissatisfaction.